Pelatihan Kesehatan Jiwa Dan Pencegahan Bunuh Diri Di Kalangan Remaja Melalui Posyandu Remaja - Mulia, Madepan; Savidni, Elvira; Rahmat, Rezqiqah Aulia; Malaha, Naomi; Hastutiningtyas, Wahidyanti Rahayu (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Adolescents are an age group vulnerable to mental health disorders due to psychological changes, academic pressures, and social issues. The surge in suicide cases among adolescents demonstrates the urgency of community-based interventions. Adolescent Integrated Health Posts (Posyandu Adolescents), as a community-based health service, can be an effective medium for mental health promotion and suicide prevention. This activity aims to increase adolescents' knowledge, skills, and awareness of the importance of mental health and recognizing early signs of psychological disorders. The implementation method used interactive training, simulations, and group discussions with Adolescent Integrated Health Post (Posyandu Adolescents) cadres. The results of the activity showed a significant increase in participants' understanding of mental health and suicide prevention. This program is recommended for replication in various regions as a promotive and preventive measure.